Desempenho do milho em consórcio com diferentes espécies forrageiras tropicais - Agostini, Andressa Carla (2016)
Crop-animal System is a system with emphasis on the recovery of degraded areas and aims to maximize the use of land to produce greater quantities of biomass. It allows the cultivation of different plant species in the same area, time and / or space. The combination of corn and forage is important in this system. It ensures to the producer diversity in the income and guarantee the system's sustainability. In this context, the aim of this work is to evaluate an alternative combination of corn and forage in the southwest of Paraná, in a subtropical climate.The plantation of crop with Brachiaria Ruziziensis, Brachiaria Brizantha cv. Piatã,and Panicum Macimum cv. Aruana, was at the beginning of October 2014. The experiment was arranged in four repetitions. We evaluated the production of dry matter (DM) of maize silage point, total biomass, the forage yield components for corn productivity and nitrogen in the tissue of both species. Productivity of corn silage there was no significant difference between the treatments, but, Corn + B. Ruziziensis in the grain yield it was the treatment with lower production, with only 5486.88 kg ha-1. In the production of corn silage + forage, treatment Corn + B. Ruziziensis showed higher DM production, 21,502.5 kg ha-1, followed by treatment Corn + B. Brizantha cv. Piatã with 21,192.6 kg ha-1 DM, and treatment Corn + P. Maximum cv. Aruana with lower production. It was observed that the higher the forage biomass productivity, the smaller the grain yield in forage consortium treatments. There is a greater efficiency in the production of silage when there is a greater increase in forage. In the three forage cutting times, Corn + B. Ruziziensis treatment obtained higher biomass yield. In the case of nitrogen competition, the results were not significant for both treatments compared with single corn, there was no competition from forage with the corn crop by nutrient. The P. Maximum cv. Aruana got a lower rate in the production of biomass, but the question crude protein was the highest percentages estimated 165.6 g kg-1, leading the producer to have good alternatives as their primary goal. In the case of biomass, the Corn+ B.Ruziziensis treatment would be a good alternative to incrementing straw to the soil and also for beef cattle activity. On protein, Corn fits+ P. Maximum cv. Aruana, it’s great for dairy farming that has great prominence in the Paraná Southwest region.